Peacekeeping in South Lebanon : credibility and local cooperation - Newby, Vanessa F. (Syracuse studies on peace and conflict resolution., 2018)
Although the concept of credibility has been identified by the United Nations as a significant factor in successful peacekeeping operations, its role has largely been ignored in the literature on peacekeeping at the local level. In this book, Newby provides the first detailed examination of credibility's essential place in peacekeeping. With empirically rich analysis, Newby explores the United Nations Interim Force in Lebanon (UNIFIL) and its navigation of political tensions in one of the world's geopolitical flashpoints, a place where the mission's work is constrained by weak local legitimacy born of a complex political situation. Identifying four types of credibility--technical, material, security, and responsiveness--Newby traces the ways in which building credibility served UNIFIL and has enabled the mission to exercise its mandate despite significant challenges on the ground. Peacekeeping in South Lebanon unpacks the day-to-day business of running a peace mission and argues that credibility should be regarded as an independent construct when considering how a peacekeeping operation functions and survives.